Effects of minimum wage changes on the wage distribution in low-wage and high-wage sectors - Strawiński, Paweł; Majchrowska, Aleksandra (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: The research aims to compare the effects of a change in the national minimum wage on the wage distribution in the low and high-paid economic sectors. We assess how wages in different economic sectors react to the minimum wage policy established at the national level. Methodology: We use individual wages and employment characteristics data from the Structure of Earnings Survey in Poland. The methodology applied in this study uses reweighting decomposition based on the non-parametric approach of DiNardo et al. (1996). Results: The results showed that minimum wage growth impacts economic sectors differently. In low-wage sections, minimum wage legislation forced wage growth in the left tail of the wage distribution. Up to the third decile, wage growth was equal to minimum wage growth. Moreover, the results indicated the significantly varying lengths of the spill-over effects across the analysed NACE sections. We found strong spill-over effects in low-wage sections on the entire wage distribution. In the high-wage sector, we did not observe the spill-over effects of a minimum wage increase. Implications and recommendations: Our results are important from both the theoretical and practical points of view as they explain why the literature reports conflicting evidence regarding the impact of minimum wage changes on wage distribution and the presence of the spill-over effects. Our results indicate that the most important reason is that national minimum wage increases affect wages in different parts of the economy to different extents, and thus are beneficial for the policymakers. They show that from the point of view of the policy of compressing wage inequalities, the effects of raising the minimum wage turned out to be not so obvious. Originality/value: According to our knowledge, this is the first study on the impact of minimum wage on wage distribution at the NACE economic section level.
Argumenta Oeconomica, 2025, Nr 1 (54), s. 170-186
Keywords: minimum wage; low-wage sector; wage distribution; spill-over effects